2018
DOI: 10.4997/jrcpe.2018.405
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Psychosocial Rehabilitation in Palliative Care

Abstract: Palliative care is an integrated approach that promotes the quality of life of patients and families who are confronted with the physical, psychosocial and spiritual problems associated with a life-threatening illness. 1 The palliative patient is not necessarily a terminal patient (estimated prognosis of 3-6 months), or a moribund or agonising patient (estimated prognosis of days or hours). 1 According to the World Health Organization (WHO) and the National Plan of Palliative Care, palliative care: affi rms li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
2
0
2
Order By: Relevance
“…[ 42 ] According to another definition palliative care is “an integrated approach that promotes the QoL of patients and families who are confronted with the physical, psychosocial and spiritual problems associated with a life-threatening illness” . [ 43 ] It is further elaborated as a form of care that “affirms life and accepts death as a natural process without trying to delay the process and constitutes a global and holistic approach to the patients suffering from a physical, psychological, social and spiritual point of view; seeks the well-being and QoL of the patient, is centered on the needs of patients and their families, life and death, that should not be restricted to terminally ill and agonized patients and should be addressed by a multidisciplinary team”. It is critical to remember that palliative care is focused on the patient's requirements, not on the likelihood of recovery.…”
Section: Treatment Models Focusing On Well-being and Qolmentioning
confidence: 99%
“…[ 42 ] According to another definition palliative care is “an integrated approach that promotes the QoL of patients and families who are confronted with the physical, psychosocial and spiritual problems associated with a life-threatening illness” . [ 43 ] It is further elaborated as a form of care that “affirms life and accepts death as a natural process without trying to delay the process and constitutes a global and holistic approach to the patients suffering from a physical, psychological, social and spiritual point of view; seeks the well-being and QoL of the patient, is centered on the needs of patients and their families, life and death, that should not be restricted to terminally ill and agonized patients and should be addressed by a multidisciplinary team”. It is critical to remember that palliative care is focused on the patient's requirements, not on the likelihood of recovery.…”
Section: Treatment Models Focusing On Well-being and Qolmentioning
confidence: 99%
“…Bei der Palliativmedizin geht es nicht nur ausschließlich um Patient*innen mit einer geschätzten Lebenserwartung von wenigen Stunden oder Monaten [2]. Die Aufgabe der Palliativmedizin besteht nicht darin, das Sterben zu beschleunigen oder zu verändern [3].…”
Section: Multiresistente Erreger In Der Stationären Palliativmedizinunclassified
“…Auf einer Palliativstation müssen neben der ständigen medizinischen und pflegerischen Versorgung auch soziale Interaktion und Unterstützung sowie Geselligkeit und Freizeit sichergestellt werden [2], um der psychischen Belastung entgegenzuwirken. Eine psychische Belastung bezieht sich auf einen Zustand des emotionalen Leids, das durch das Auftreten von Depression und Angst gekennzeichnet ist [9].…”
Section: Multiresistente Erreger In Der Stationären Palliativmedizinunclassified
“…The community-based rehabilitation model has the potential to expand. Different rehabilitation services like yoga & physical exercise, peer discussions, trainings include with living skills, social skills, vocational skills, social skills, individual and family counseling can lead to psychosocial rehabilitation people diagnosed with psychosis, bipolar, schizophrenia, depression and intellectual disability (Almada, Casquinha, Cotovio, Santos, & Caixeiro, 2018;McKay, Nugent, Johnsen, Eaton, & Lidz, 2018). Barton (2018), Systematic review found that psychosocial interventions & counseling to infertile patients helps to improve wellbeing and pregnancy rates.…”
Section: Counseling and Psychosocial Skillsmentioning
confidence: 99%